Permian bivalves of the Taciba Formation, Itarare group, Parana basin, and their biostratigraphic significance - Simões, Marcello Guimarães [UNESP]; Peixoto Neves, Jacqueline; Anelli, Luiz Eduardo; Weinschuetz, Luiz Carlos (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2012)
A small and poorly diversified bivalve fauna from Taciba Formation, Itarare Group, Parana Basin (State of Santa Catarina, Mafra Municipality), is described in this paper for the first time, based on new findings. The fauna is recorded in a 30 cm thick interval of fine sandstone locally at the top of Taciba Formation, in the Butia quarry. The studied fossil-bearing sand-stone bed is a marine intercalation recording a brief eustatic rise in sea-level, probably following glacier retreat and climate amelioration at the end of a broad glacial scenario. The fauna is mainly dominated by productid brachiopods, which are not described here, and rare mollusk shells (bivalves and gastropods). Two bivalve species were identified: Myonia argentinensis (Harrington, 1955), and Aviculopecten multiscalptus (Thomas, 1928). The presence of Myonia argentinensis is note-worthy since this species is also present in the Baitaca assemblage found in marine siltstones (Baitaca assemblage) of the Rio do Sul Formation, cropping out at the Teixeira Soares region, Parana State. This species is also recorded in the bivalve fauna from the Bonete Formation, Pillahinco Group, Sauce Grande Basin, Buenos Aires Province, in Argentina. Hence, the marine bivalves of the Taciba Formation are associated with the transgressive event that characterizes the Eurydesma fauna, indicating a Late Asselian-Sakmarian age for the bivalve fauna. Presence of the Myonia argentinensis megadesmid species reinforces the Gondwanic nature of the studied fauna.